A cellulose microsphere adsorbent and preparation method thereof

By adding surfactant to the preparation of cellulose microspheres and carrying out hydrothermal epoxy cross-linking reaction, the problem of low porosity of cellulose microspheres is solved, and its bioadsorption performance is significantly improved, especially for β2-micro The adsorption rate of globulin reaches more than 90%.

CN116284964BActive Publication Date: 2025-02-07JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310093960.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2025-02-07
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

The porosity of existing cellulose microsphere materials is not high, resulting in poor bioadsorption performance.

Method used

The porosity of the microspheres is increased by adding surfactant during the preparation of cellulose microspheres, and the surface pore size of the microspheres is adjusted through hydrothermal epoxy cross-linking reaction.

Benefits of technology

The porosity and bioadsorption performance of cellulose microspheres are significantly improved, and the adsorption rate of β2-microspheres can be achieved at a rate higher than 90% while controlling the adsorption rate of total protein and albumin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284964B_ABST
    Figure CN116284964B_ABST
Patent Text Reader

Abstract

A cellulose microsphere adsorbent and a preparation method thereof, belonging to the technical field of cellulose microsphere preparation. Cellulose triacetate or diacetate is used as a raw material to prepare a cellulose acetate solution; then an oil phase porogen and an oil phase surfactant are added, and after uniform mixing, a clear and transparent cellulose mixed solution is obtained, which is then added to an aqueous solution of hydrophilic polymers such as polyethylene glycol and polyvinyl alcohol to disperse the oil phase and form cellulose droplets; after evaporating the solvent, the cellulose acetate microspheres are filtered, washed with water and sieved to obtain cellulose acetate microspheres, which are then hydrolyzed in a NaOH solution and washed thoroughly with water to obtain a cellulose microsphere adsorbent. In the static adsorption experiment of β2-microglobulin, the cellulose microsphere adsorbent of the present invention can achieve an adsorption rate of more than 90% for β2-microglobulin, which is harmful to the human body, while controlling the adsorption rate of total protein to less than 5% and the adsorption rate of albumin to less than 7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cellulose microsphere preparation, and in particular relates to a cellulose microsphere adsorbent and a preparation method thereof. The cellulose microsphere can be used for adsorption of biological molecules. Background Art

[0002] The preparation of cellulose materials has always been an important research area in chemistry, chemical engineering, biochemistry, and related fields involving chemical design of biomaterials. Cellulose itself has the advantages of good mechanical properties, excellent chemical properties, abundant and renewable natural reserves, good biocompatibility and sustainability. Each repeating unit of the cellulose structure has three hydroxyl groups, so it is possible to introduce functional groups through reactions with hydroxyl groups for chemical modification, which can change the properties of cellulose from hydrophilic to hydrophobic, or from non-charged to anionic or cationic. Modified cellulose can also be mixed with organic or inorganic compounds to prepare functional materials with specific applications.

[0003] Cellulose microspheres (CM) are spherical particles with diameters in the micrometer range or even in the millimeter range. They are used in many applications, from chromatography fillers, protein fixation to delayed drug release. In the past few decades, many methods and preparation processes for preparing cellulose microspheres have been reported. These methods and processes include the use of different solvents, molding techniques, and technical equipment for mass production. Especially since the 1980s, people have found that cellulose microsphere materials can have good adsorption properties in biosorption. In addition, cellulose microsphere materials themselves are green, biocompatible, and renewable. Therefore, in recent years, people have continuously explored and optimized the application of cellulose microsphere materials in biosorption.

[0004] The cellulose microsphere materials currently used for biosorption are often limited by their low porosity, resulting in adsorption performance that does not meet expectations. Therefore, the design and preparation of cellulose microspheres with high porosity and adjustable pore size is the key to optimizing cellulose microsphere materials. Studies have found that the porosity of cellulose microspheres can be greatly improved through the interaction between oil-phase porogens and oil-phase surfactants, thereby solving the problem of poor biosorption performance caused by low porosity of cellulose microspheres. Summary of the invention

[0005] The purpose of the present invention is to provide a cellulose microsphere adsorbent and a preparation method thereof. In the preparation process of the cellulose microspheres, the porosity of the cellulose microspheres can be greatly increased by adding a surfactant, so that they can be better used for biomolecules. For cellulose microspheres with high porosity, the surface pore size of the microspheres can also be adjusted by a hydrothermal epoxy cross-linking reaction.

[0006] In Beta 2In the static adsorption experiment of microglobulin, the cellulose microspheres of the present invention can achieve the adsorption rate of total protein below 5% and albumin below 7%, while at the same time, the β-actin that is harmful to the human body is reduced. 2 -The adsorption rate of microglobulin reaches more than 90%.

[0007] The method for preparing a high-porosity cellulose microsphere adsorbent according to the present invention comprises the following steps:

[0008] 1. Preparation of cellulose microsphere adsorbent by stirring dispersion regeneration method

[0009] The invention relates to a method for preparing a cellulose acetate solution with a mass fraction of 5 to 15% of cellulose acetate or cellulose diacetate by using triacetyl cellulose or cellulose diacetate (CA) as a raw material and one or two of chlorinated hydrocarbons, anhydrous ethanol and acetone as a mixed solvent; then adding an oil phase porogen and an oil phase surfactant, wherein the oil phase porogen is two or three of an alcohol with a carbon number of 7 to 12, diacetin, triacetin and 1,2-ethylene glycol diacetate, and the oil phase surfactant is one or two of OP-4, OP-7, Span-80 and 1-dodecene; mixing uniformly to obtain a clear and transparent cellulose mixed solution, and then adding the mixed solution to the mixture. The cellulose acetate microspheres are prepared by adding the cellulose acetate microspheres into an aqueous solution containing a hydrophilic polymer such as polyethylene glycol and polyvinyl alcohol, stirring and dispersing at 20 to 30°C for 3 to 15 hours to disperse the oil phase into cellulose droplets; then heating in a water bath at 35 to 45°C for 10 to 36 hours to evaporate the solvent, filtering, washing with water, and sieving on sieves of different specifications according to the particle size of the microspheres to obtain cellulose acetate microspheres with a particle size of 250 to 500 μm, wherein the volume ratio of the oil phase porogen to the cellulose acetate solution is 0.2 to 0.5:1, and the volume ratio of the oil phase surfactant to the oil phase porogen is 0 to 0.2:1; finally, the obtained cellulose acetate microspheres are heated and hydrolyzed in a 2 mol / L NaOH solution at 50 to 70°C for 2 to 4 hours, and the cellulose microsphere adsorbent is obtained after being fully washed with water, and stored at room temperature away from light for later use.

[0010] 2. Regulating the surface pore size of cellulose microsphere adsorbent by hydrothermal epoxy crosslinking

[0011] Take cellulose microsphere adsorbent and add it to the polytetrafluoroethylene hydrothermal reactor lining, then add sodium hydroxide solution and epichlorohydrin, wherein the volume ratio of epichlorohydrin to cellulose microsphere is 0.05-0.5:1, the volume ratio of sodium hydroxide solution to cellulose microsphere is 6-10:1, and the concentration of NaOH solution is 0.5 mol / L; perform hydrothermal epoxy crosslinking (the reaction temperature of hydrothermal epoxy crosslinking is 100-140°C, and the reaction time is 1-3 hours), so as to adjust the surface pore size of cellulose microsphere; the hydrothermal epoxy crosslinking reaction formula of cellulose microsphere is as follows:

[0012] BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 : Optical microscope photo of cellulose microspheres CM-8 prepared by the present invention;

[0014] Figure 2 :Scanning electron microscope photos of cellulose microspheres ( Figure 2 a and Figure 2 b Scanning electron micrographs of the surface and cross section of CM-7, respectively; Figure 2 c and Figure 2 d are scanning electron micrographs of the surface and cross section of CM-8, respectively);

[0015] Figure 3 : Average pore size distribution curve of cellulose microspheres CM-1 (the abscissa is the microsphere pore size, and the ordinate is the differential mercury intrusion, i.e., the pore volume value);

[0016] Figure 4 : Fourier transform infrared spectra of cellulose microspheres CM-7, CM-8 and cellulose triacetate (CA).

[0017] Figure 5 : Thermogravimetric analysis and X-ray diffraction patterns of cellulose microspheres before and after cross-linking. Figure 5 a is the thermogravimetric analysis spectrum of CM-7, the horizontal axis is temperature (℃), the left vertical axis is mass percentage, and the right vertical axis is mass change rate; Figure 5 b is the thermogravimetric analysis spectrum of CM-8, the horizontal axis is temperature (°C), the left vertical axis is mass percentage, and the right vertical axis is mass change rate; Figure 5 c is the X-ray diffraction spectra of CM-8, CM-7 and CM-7 subjected to only hydrothermal reaction (without the addition of epichlorohydrin) (the order of the spectra is from top to bottom), the abscissa is the diffraction angle (2θ), and the ordinate is the X-ray diffraction intensity.

[0018] Figure 6 : Adsorption performance kinetic curve of microsphere 8 (abscissa is time, ordinate is adsorption rate; TP is total protein, ALB is albumin, β 2 -MG is β 2 -microglobulin).

[0019] Table 1. Pore size data of cellulose microspheres tested by mercury intrusion method

[0020] Sample No. <![CDATA[Pore volume (cm 3 / g)]]> Average pore size (nm) Porosity CM-1 2.2199 328.6 11.6738% CM-7 3.2506 544.7 81.5172% CM-8 2.3160 327.6 74.8884%

[0021] From the data in Table 1, we can see that the porosity of CM-7 and CM-8 is much higher than that of CM-1, indicating that the porosity of cellulose microspheres can be effectively improved by adding surfactants. Secondly, by comparing the average pore sizes of CM-7 and CM-8, the hydrothermal epoxy crosslinking of cellulose microspheres under alkaline conditions can control the pore size of the microspheres. Figure 2 a and Figure 2 From the comparison of the electron scanning micrographs in c, the surface pore size of CM-8 is obviously smaller than that of CM-7.

[0022] Table 2. Total protein, albumin, β 2 - Adsorption rate of microglobulin

[0023]

[0024]

[0025] Note: c(before adsorption) refers to the concentration of each protein before static adsorption; c(after adsorption) refers to the concentration of each protein after static adsorption.

[0026] From the data in Table 2, we can see that the β 2 -The protein adsorption rate of microspheres is significantly higher than that of CM-1, which indicates that increasing the porosity of microspheres can effectively increase β 2 - microglobulin adsorption rate, can improve the efficiency to remove biotoxin molecules in the human body; CM-7 has a higher adsorption rate for total protein and albumin due to its larger surface pore size, while CM-8 reduces the surface pore size through hydrothermal epoxy cross-linking reaction. Combined with the adsorption data, it shows that while ensuring β 2 - Microglobulin has a high adsorption rate, which effectively reduces the adsorption rate of total protein and albumin, and improves the adsorption of β 2 -Selective adsorption efficiency of microglobulins. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below with reference to specific embodiments, but the present invention is not limited thereto.

[0028] Example 1

[0029] Weigh 64 g of cellulose triacetate powder, dissolve it in a mixed solvent of 378 mL of chlorinated hydrocarbons and 42 mL of anhydrous ethanol, and stir until completely dissolved to obtain a cellulose acetate mixed solution. Measure 144 mL of 1,2-ethylene glycol diacetate and 36 mL of n-heptanol and add them to the above mixed solution. After oscillating and mixing evenly, add the obtained mixed solution to 2.4 L of a 1% polyethylene glycol aqueous solution, and stir and disperse it at 250 rpm for 12 hours at 25 ° C for shaping. After stirring and shaping, heat it in a 40 ° C water bath for 24 hours to volatilize the mixed solvent, and finally filter, wash with water, and sieve it on sieves of different specifications according to the particle size of the microspheres to obtain microspheres with a particle size of 250 to 500 μm. Finally, the obtained microspheres are first heated and hydrolyzed at 60 ° C in a 2 mol / L NaOH solution for 2 hours, and then washed with water to obtain cellulose microspheres, which are stored at room temperature away from light for later use, and are recorded as microspheres 1 (CM-1).

[0030] The prepared microspheres had good morphology ( Figure 1 ), the particle size of the microspheres is 250-500 μm. In the mercury intrusion test, the average pore size of the microspheres is 328.6 nm and the pore volume is 2.2199 cm 3 / g, the porosity is only 11.6738%. In the pore size distribution curve ( Figure 3 ), it can be seen that the pore size of the microspheres is below 1 μm, which meets the basic requirements of biomolecule adsorption materials for pore size.

[0031] Example 2

[0032] Weigh 80g of cellulose triacetate powder, dissolve it in a mixed solvent of 378mL of chlorinated hydrocarbons and 42mL of anhydrous ethanol, and stir until completely dissolved to obtain a cellulose acetate mixed solution. Measure 144mL of 1,2-ethylene glycol diacetate and 36mL of n-heptanol and add them to the above mixed solution. After oscillating and mixing evenly, add the obtained mixed solution to 2.4L of 1% polyethylene glycol aqueous solution, and stir and disperse it at 250 rpm at 25°C for 12h for shaping. After stirring and shaping, heat it in a 40°C water bath for 24h to volatilize the mixed solvent, and finally filter, wash it with water, and sieve it on sieves of different specifications according to the particle size of the microspheres to obtain microspheres with a particle size of 250-500μm. Finally, the obtained microspheres are first heated and hydrolyzed at 60°C in a 2mol / L NaOH solution for 2h, and then washed with water to obtain cellulose microspheres, which are stored at room temperature away from light for later use, and are recorded as microspheres 2 (CM-2).

[0033] Example 3

[0034] Weigh 32g of cellulose triacetate powder, dissolve it in a mixed solvent of 378mL of chlorinated hydrocarbons and 42mL of anhydrous ethanol, and stir until completely dissolved to obtain a cellulose acetate mixed solution. Measure 144mL of 1,2-ethylene glycol diacetate and 36mL of n-heptanol and add them to the above mixed solution. After oscillating and mixing evenly, add the obtained mixed solution to 2.4L of 1% polyethylene glycol aqueous solution, and stir and disperse at 250 rpm for 12h at 25°C for shaping. After stirring and shaping, heat it in a 40°C water bath for 24h, and finally filter, wash it with water, and sieve it on sieves of different specifications according to the particle size of the microspheres to obtain microspheres with a particle size of 250-500μm. Finally, the obtained microspheres are first heated and hydrolyzed at 60°C in a 2mol / L NaOH solution for 2h, and then washed with water to obtain cellulose microspheres, which are stored at room temperature away from light for later use, and are recorded as microspheres 3 (CM-3).

[0035] Example 4

[0036] Weigh 64 g of cellulose triacetate powder, dissolve it in a mixed solvent of 414 mL of chlorinated hydrocarbons and 46 mL of acetone, and stir until completely dissolved to obtain a cellulose acetate mixed solution. Measure 112 mL of 1,2-ethylene glycol diacetate and 28 mL of n-heptanol and add them to the above mixed solution. After oscillating and mixing evenly, add the obtained mixed solution to 2.4 L of a 1% polyethylene glycol aqueous solution, and stir and disperse it at 250 rpm for 12 hours at 25 ° C for shaping. After stirring and shaping, heat it in a 40 ° C water bath for 24 hours, and finally filter, wash it with water, and sieve it on sieves of different specifications according to the particle size of the microspheres to obtain microspheres with a particle size of 250 to 500 μm. Finally, the obtained microspheres are first heated and hydrolyzed at 60 ° C in a 2 mol / L NaOH solution for 2 hours, and then washed with water to obtain cellulose microspheres, which are stored at room temperature away from light for later use, and are recorded as microspheres 4 (CM-4).

[0037] Example 5

[0038] Weigh 64 g of cellulose triacetate powder, dissolve it in a mixed solvent of 450 mL of chlorinated hydrocarbons and 50 mL of acetone, and stir until completely dissolved to obtain a cellulose acetate mixed solution. Measure 80 mL of 1,2-ethylene glycol diacetate and 20 mL of n-heptanol and add them to the above mixed solution. After oscillating and mixing evenly, add the obtained mixed solution to 2.4 L of a 1% polyethylene glycol aqueous solution, and stir and disperse it at 250 rpm for 12 hours at 25 ° C for shaping. After stirring and shaping, heat it in a 40 ° C water bath for 24 hours, and finally filter, wash it with water, and sieve it on sieves of different specifications according to the particle size of the microspheres to obtain microspheres with a particle size of 250 to 500 μm. Finally, the obtained microspheres are first heated and hydrolyzed at 60 ° C in a 2 mol / L NaOH solution for 2 hours, and then washed with water to obtain cellulose microspheres, which are stored at room temperature away from light for later use, and are recorded as microspheres 5 (CM-5).

[0039] Example 6

[0040] Weigh 80g of cellulose triacetate powder, dissolve it in a mixed solvent of 450mL of chlorinated hydrocarbons and 50mL of acetone, and stir until completely dissolved to obtain a cellulose acetate mixed solution. Measure 80mL of 1,2-ethylene glycol diacetate and 20mL of n-heptanol and add them to the above mixed solution. After oscillating and mixing evenly, add the obtained mixed solution to 2.4L of 1% polyethylene glycol aqueous solution, and stir and disperse at 250 rpm for 12h at 25°C for shaping. After stirring and shaping, heat in a 40°C water bath for 24h, and finally filter, wash with water, and sieve on sieves of different specifications according to the particle size of the microspheres to obtain microspheres with a particle size of 250-500μm. Finally, the obtained microspheres are first heated and hydrolyzed at 60°C in a 2mol / L NaOH solution for 2h, and then fully washed with water to obtain cellulose microspheres, which are stored at room temperature away from light for later use, and are recorded as microspheres 6 (CM-6).

[0041] Example 7

[0042] Weigh 64g of cellulose triacetate powder, dissolve it in a mixed solvent of 378mL of chlorinated hydrocarbons and 42mL of anhydrous ethanol, and stir until completely dissolved to obtain a cellulose acetate mixed solution. Measure 140mL of 1,2-ethylene glycol diacetate and 34mL of n-heptanol and add them to the above mixed solution. After oscillating and mixing evenly, add 6mL of oil-phase surfactant OP-7, add the obtained mixed solution to 2.4L of 1% polyethylene glycol aqueous solution, and stir and disperse at 250 rpm for 12h at 25°C for shaping. After stirring and shaping, heat in a 40°C water bath for 24h, and finally filter, wash with water, and sieve on sieves of different specifications according to the particle size of the microspheres to obtain microspheres with a particle size of 250-500μm. Finally, the obtained microspheres are first heated and hydrolyzed at 60°C in a 2mol / LNaOH solution for 2h, and then washed with water to obtain cellulose microspheres, which are stored at room temperature away from light for later use, and are recorded as microspheres 7 (CM-7).

[0043] The morphology of cellulose microspheres was analyzed by scanning electron microscopy ( Figure 2 a and Figure 2 b), we can see the surface of the microspheres ( Figure 2 a) There are many pores, and the surface pores are all below 1μm, and the interior ( Figure 2 b) also presents a porous structure, which is conducive to improving adsorption performance. In the mercury intrusion test ( Figure 3 ), the average pore size of the microspheres is 544.7 nm, and the pore volume is 3.2506 cm 3 / g, the porosity is greatly improved, from 11.6738% to 81.5172% (as shown in Table 1).

[0044] Example 8

[0045] Weigh 64g of cellulose triacetate powder, dissolve it in a mixed solvent of 378mL of chlorinated hydrocarbons and 42mL of anhydrous ethanol, stir until completely dissolved, and obtain a cellulose acetate mixed solution. Measure 140mL of 1,2-ethylene glycol diacetate and 34mL of n-heptanol and add them to the above mixed solution. After oscillating and mixing evenly, add 6mL of oil-phase surfactant OP-7, add the obtained mixed solution to 2.4L of 1% polyethylene glycol aqueous solution, and stir and disperse at 250 rpm for 12h at 25°C for shaping. After stirring and shaping, heat in a 40°C water bath for 24h, and finally filter, wash with water, and sieve on sieves of different specifications according to the particle size of the microspheres to obtain microspheres with a particle size of 250-500μm. Finally, the obtained microspheres are first heated and hydrolyzed at 60°C in a 2mol / LNaOH solution for 2h, and then washed with water to obtain cellulose microspheres, which are stored at room temperature away from light for later use.

[0046] 5 mL of cellulose microspheres were added to a 50 mL polytetrafluoroethylene hydrothermal reactor liner, and then 40 mL of 0.5 mol / L NaOH solution and 0.4 mL of epichlorohydrin (ECH) were added. After reacting at 120 °C for 2 h, the microspheres were taken out and naturally cooled to room temperature. The obtained cellulose microspheres were fully washed with water and stored in the dark at room temperature for later use. They were recorded as microspheres 8 (CM-8).

[0047] By comparing the results before and after cross-linking, that is, the thermogravimetric analysis of CM-7 (before cross-linking) and CM-8 (after cross-linking), it can be found that the surface pore size of CM-8 microspheres becomes smaller and the internal pore size structure becomes more compact. The data of the porosity and average pore size of the microspheres tested by mercury intrusion also show that after hydrothermal epoxy cross-linking, the average pore size of the microspheres decreases from 544.7nm to 327.6nm, and its porosity also decreases from 81.5172% to 74.8884%. This allows the bioadsorption material to maintain a better ability to screen biological molecules and have a high adsorption rate for target toxin molecules. Through the infrared spectra of the microspheres before and after hydrothermal epoxy cross-linking ( Figure 4 ) by comparison, it can be found that the infrared spectrum of the microspheres after hydrothermal epoxy crosslinking is 1000-1100cm -1 The COC characteristic peak at the position is significantly enhanced, indicating that more ether bonds are generated. Figure 5 a) and after cross-linking ( Figure 5 b) Thermogravimetric analysis spectrum and X-ray diffraction spectrum ( Figure 5 c) By comparison, it was found that the structure of the microspheres after cross-linking was more simple and compact, and in the X-ray diffraction pattern, the sharper the diffraction peak, the more regular the crystal form of the sample and the tighter the internal structure of the microspheres.

[0048] Example 9: Static adsorption of microspheres

[0049] The microspheres prepared in the above embodiment are only used as an adsorption carrier and have no specific adsorption to biomolecules. They need to be grafted with ligands to selectively adsorb the corresponding biomolecules. Therefore, it is necessary to functionalize the microspheres, i.e., graft ligands, in order to be able to adsorb β 2 -Microglobulin (β 2-MG), it is necessary to graft hydrophobic ligands on the microspheres: take 10mL of the above-prepared cellulose microspheres in a 250mL ground-mouth conical flask, drain the water, add epichlorohydrin and 2mol / L NaOH solution in a ratio of 5:10:2 of cellulose microspheres: 2mol / LNaOH solution: epichlorohydrin (ECH), heat at 40°C, start shaking, the shaking rate is 120rpm, and react for 2h. After the reaction, wash it with deionized water for use. Drain the water of the cellulose microspheres, rinse them with ethanol solution 3 times and then drain them, then add 40mL, 10mg / mL hexadecylamine ethanol solution, heat and shake at 60°C for 12h, wash them with ethanol first, then wash them with deionized water, wash them clean and store them away from light at room temperature for use.

[0050] Preparation of β 2 -The concentration of microglobulin in the bovine plasma to be tested is about 10 mg / L. 1 mL of functionalized CM-1, CM-7, and CM-8 microspheres were measured and placed in a 250 mL conical flask. After absorbing the water, they were rinsed with PBS buffer solution for 3 times, and 100 mL of the prepared bovine plasma to be tested was added. The static adsorption was performed at 37 ° C with an oscillation rate of 150 rpm for 2 hours. Then 1 mL of the bovine plasma to be tested was taken, and the supernatant was tested to obtain the total protein (TP), albumin (ALB), β 2 -Microglobulin (β 2 -MG) concentration, and then the adsorption rate of each protein was obtained (as shown in Table 2).

[0051] Preparation of β 2 -The concentration of microglobulin in the bovine plasma to be tested is about 15 mg / L. Measure 10 mL of functionalized modified CM-8 microspheres in a 250 mL conical flask, absorb the water, rinse with PBS buffer solution 3 times, add 100 mL of the prepared bovine plasma to be tested, and perform static adsorption at a temperature of 37°C and an oscillation rate of 150 rpm. Take 1 mL of the bovine plasma to be tested at 0, 10, 20, 30, 40, 50, 60, 90, 120, 150, and 180 minutes of static adsorption, and take the supernatant for detection to obtain the total protein (TP), albumin (ALB), β 2 -Microglobulin (β 2 -MG) concentration, and then the adsorption rate of each protein was obtained. Then, a static adsorption kinetic curve was drawn with "time" as the X-axis and "protein concentration / initial protein concentration × 100%" as the Y-axis ( Figure 6 ), according to the adsorption results, at 180 min of adsorption, the adsorption rate of the functionalized CM-8 microspheres for total protein (TP) was ≤5%, the adsorption rate for albumin (ALB) was ≤7%, and the adsorption rate for β 2 -Microglobulin (β2 -MG) adsorption rate ≥90%.

Claims

1. A method for preparing a cellulose microsphere adsorbent, characterized in that: The method comprises the following steps: using triacetyl cellulose or diacetyl cellulose as raw materials, using one or two of chlorinated hydrocarbons, anhydrous ethanol and acetone as mixed solvents, preparing a cellulose acetate solution with a mass fraction of 5 to 15% of triacetyl cellulose or diacetyl cellulose; then adding an oil phase porogen and an oil phase surfactant, mixing evenly to obtain a clear and transparent cellulose mixed solution, adding the mixed solution to a hydrophilic polymer aqueous solution containing polyethylene glycol or polyvinyl alcohol, stirring and dispersing at 20 to 30° C. for 3 to 15 hours, and dispersing the oil phase into cellulose droplets; then heating in a water bath at 35 to 45° C. for 10 to 20 minutes, and then heating the mixture to a temperature of 35 to 45° C. for 10 to 25 minutes. The solvent is evaporated for 36 hours, and then filtered, washed with water and sieved to obtain cellulose acetate microspheres with a particle size of 250-500 μm, wherein the volume ratio of the oil phase porogen to the cellulose acetate solution is 0.2-0.5:1, and the volume ratio of the oil phase surfactant to the oil phase porogen is 0-0.2:1; finally, the obtained cellulose acetate microspheres are heated and hydrolyzed in a 2 mol / L NaOH solution at 50-70° C. for 2-4 hours, and the cellulose microsphere adsorbent is obtained after being fully washed with water; wherein the oil phase surfactant is OP-7, and the volume amount of the oil phase surfactant is not 0.

2. The method for preparing a cellulose microsphere adsorbent according to claim 1, characterized in that: The oil phase porogen is two or three of alcohols having 7 to 12 carbon atoms, diacetin, triacetin, and 1,2-ethylene glycol diacetate.

3. The method for preparing a cellulose microsphere adsorbent according to claim 1, characterized in that: Cellulose microspheres are added to a polytetrafluoroethylene hydrothermal reactor lining, and then sodium hydroxide solution and epichlorohydrin are added, wherein the volume ratio of epichlorohydrin to cellulose microspheres is 0.05-0.5:1, the volume ratio of sodium hydroxide solution to cellulose microspheres is 6-10:1, and the concentration of NaOH solution is 0.5 mol / L; hydrothermal epoxy cross-linking is performed to adjust the surface pore size of the cellulose microspheres.

4. The method for preparing a cellulose microsphere adsorbent according to claim 3, characterized in that: The reaction temperature of the hydrothermal epoxy crosslinking is 100 to 140° C., and the reaction time is 1 to 3 hours.

5. A cellulose microsphere adsorbent, characterized in that: The method is prepared by any one of claims 1 to 4.

Citation Information

Patent Citations

  • Cellulose microsphere as well as preparation method and use thereof

    CN101250267A

  • Hollow porous cellulose microspheres as well as preparation method and application thereof

    CN110559956A